(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
As far as cyber security is concerned, it is the process of guarding against hostile assaults on internet-connected systems including computers, servers and mobile devices, as well as electronic systems and networks and the data they contain. Threats to cyber security or the digital world in general are hostile acts designed to corrupt or destroy information or disrupt digital activities. Computer viruses, data breaches, and Denial-of-Service (DoS) assaults are examples of cyber threats. Most often, cyber-attacks happen because criminals want your business financial details and customers financial details (e.g. Credit Card data) customers or staff email addresses and login credentials. Direct, indirect, veiled, and conditional threats all fall within this category. In this article, the researchers seek to offer some insight on the Big 3 forms of cyber assaults, such as Malware, Ransomware, and Phishing. Social hacking (employees still fall prey to social assaults), ransomware, using active cyber security monitoring, unpatched vulnerabilitiespoor updating, and distributed denial-of-service (DDoS) attacks were recognised as the worst cyber security threats in 2019. Although there will be a plethora of new cyber dangers and assaults by 2020, the primary cause for this is still a lack of awareness and a low level of technical proficiency. The object of this article is to make aware of the types of Cyber threats and attacks from security point of view and in order to prevent the multiplication of Cyber-crimes too in a very simple language.